2003
DOI: 10.1002/cne.10636
|View full text |Cite
|
Sign up to set email alerts
|

Differential distribution and developmental expression of synaptic vesicle protein 2 isoforms in the mouse retina

Abstract: Synaptic vesicle protein 2 (SV2), a ubiquitous synaptic vesicle protein, is known to participate in the regulation of Ca(2+)-mediated synaptic transmission, although its precise function has not been established. Three SV2 isoforms (SV2A, SV2B, SV2C) have been identified recently, each of which has a unique distribution in brain, suggesting synapse-specific functions. To determine if SV2A, -B, and -C are differentially distributed among synapses in the retina and the sequence of their development, we examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
89
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(99 citation statements)
references
References 62 publications
10
89
0
Order By: Relevance
“…Because Rab proteins confer specificity to vesicles, these results indicate that "synaptic vesicle-like vesicles" function in trafficking and secretion in general tissues. Some recent studies reported that SV2B plays an important role in maintaining tissue-specific function (15)(16)(17)(18). The tissue-specific expression of SV2B suggests that SV2B plays a role in forming the tissuespecific structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because Rab proteins confer specificity to vesicles, these results indicate that "synaptic vesicle-like vesicles" function in trafficking and secretion in general tissues. Some recent studies reported that SV2B plays an important role in maintaining tissue-specific function (15)(16)(17)(18). The tissue-specific expression of SV2B suggests that SV2B plays a role in forming the tissuespecific structure.…”
Section: Discussionmentioning
confidence: 99%
“…SV2 is known to participate in the regulation of calcium-mediated synaptic transmission and to play a role in vesicle trafficking by binding to other cell surface proteins (13,14). Although SV2 originally was reported to be expressed specifically in the central nervous system, recent studies have shown that it also is distributed in other organs (15)(16)(17). Hayashi et al (18) reported that SV2B is expressed in the microvesicles of pinealocytes, which are rich in process terminals.…”
mentioning
confidence: 99%
“…Whole mount preparations were incubated in primary antibody for 7 days at 4°C. Primary antibodies used were ➀ rabbit polyclonal antibody anti-protein kinase C (Calbiochem, San Diego, CA) at dilution 1:1000, as a marker of rod bipolar cells (Wang et al, 2003) and ➁ ribbon-specific mouse monoclonal antibody anti-CtBP2/ribeye, dilution 1:200 (BD Transduction Laboratories, San Jose, CA, 612044). For fluorescence labeling, cells were incubated with a mixture of Alexa-tagged antimouse (488 nM) and anti-rabbit (568 nM) IgG secondary antibodies (Molecular Probes, Eugene, OR, USA) at 1:1000 dilutions for 1hr at room temperature in a light-protected environment.…”
Section: Immunocytochemistry and Confocal Microscopymentioning
confidence: 99%
“…Synaptic ribbons were identified by immunostaining for CtBP2/ribeye, a structural element of the synaptic ribbon (Schmitz et al, 2000;tom Dieck et al, 2005), shown in green in Figures 1A, 1D, and 1G. Rod bipolar cells were identified by red labeling with an antibody directed against protein kinase C alpha (PKC-α) (Wang et al, 2003) in Figures 1B, 1E, and 1H. The merged images from PKC-α and CtBP2/ribeye double-labeled cells ( Figures 1C, 1F, and 1I) reveal that CtBP2 immunofluorescence (green) is prominent in the synaptic terminals of rod bipolar cells and in the inner plexiform layer of the retina (IPL), as expected.…”
Section: A Rod Bipolar Cell Contains ≈ 34 Ribbon-style Active Zonesmentioning
confidence: 99%
“…Rods and cones have the same subtypes of exocytotic and endocytotic proteins, although there are differences in their relative abundance (Sherry and Heidelberger, 2005). Also, synaptic vesicle protein 2B is found in rods and not cones (Wang et al, 2003), but its function is unclear. Despite these differences, we find the same Ca 2ϩ dependence of release from rods and cones.…”
Section: Mechanisms Underlying Slower Dark Release From Rodsmentioning
confidence: 99%